A qualitative examination of women's self-presentation and social physique anxiety during injury rehabilitation - Driediger, Molly V.; McKay, Carly D.; Hall, Craig R.; Echlin, Paul S. (Physiotherapy, 2016)
To understand women's self-presentation experiences in the rehabilitation setting, and their attitudes and preferences toward the social and physical features of the rehabilitation environment. Qualitative study. Outpatient physiotherapy clinic. Ten women (age 18 to 64) with high social physique anxiety (Social Physique Anxiety Scale score ≥25) referred for physiotherapy following acute injury. Semi-structured interviews were conducted prior to commencement of treatment, and again after a third treatment session. Participants experienced extensive self-presentational concerns that were intensified due to the nature of the physiotherapy environment. The women reported that their self-presentational anxiety did not diminish over time, and was related to others’ negative perceptions regarding their physical appearance and inability to perform exercises as well as expected. The presence of men or younger women in the clinic was identified as a barrier to appointment attendance, along with open concept clinic settings, which were associated with the most potential for evaluation. Mirrors and windows in the physiotherapy clinic were highlighted as anxiety provoking. The women suggested that they would feel apprehensive about advocating for themselves if they felt uncomfortable with the area in which they were receiving treatment, and instead used avoidance coping strategies (e.g., hiding behind equipment, preventing eye contact) to manage their anxiety. Physique-anxious women experience extensive self-presentational concerns in the rehabilitation environment, which could affect treatment adherence. Modifying the treatment setting, providing protective self-presentational strategies such as positive self-talk, and open patient–therapist communication could be implemented to help mitigate these concerns.